Impressions of a multiple station speech and language therapy admissions interview : a thesis presented in partial fulfilment of the requirements for the degree of Master degree in Speech and Language Therapy at Massey University, Albany, New Zealand - Cope, Petronella Yvonne (Massey University, 2014)
Interviews are commonly used as part of the admissions process into selected entry university programmes to assist the selection committee to ascertain applicants’ personal qualities such as their communication skills. There are no published studies on the effectiveness of interviews for selecting applicants into speech and language therapy programmes. Concerns have been raised in other disciplines, however, regarding the value of interviews due to questions about their reliability and validity. Eva, Rosenfeld, Reiter, and Norman (2004) developed a reliable and valid interview assessment process for admission into a medical school. The process is the multiple mini-interview (MMI) consisting of short stations. A Speech and Language Therapy Multiple Mini-Interview (SLTMMI) was developed. This involved adapting Eva et al.’s (2004) MMI for the speech and language therapy context, that is, each station was developed to assess one or more of the personal attributes or skills required for the speech and language therapy profession. The research study investigated the SLTMMI’s potential acceptability for use as an admissions interview process for the Bachelor of Speech and Language Therapy (BSLT) programme at Massey University. The participants for this study were some of the student applicants for the 2013 Year 1 BSLT programme and some of the interviewers. Questionnaires were used to gather information on the participants’ experiences. In addition, all of the deidentified student applicants’ scoresheets were examined to evaluate the potential value of each station and the strength of the relationship between stations. This research study represents the first step in the process of developing an improved admissions interview process for the BSLT programme at Massey University. The findings of the study have already led to refinements of the SLTMMI and will lead to further research into its reliability and its predictive validity for academic and clinical competence.
Keywords: Speech therapists; Training; Admission; Interviews; Health occupations schools; Universities and colleges